oPtImALISASI PeRAn ZAkAt dALAm memBeRdAYAkAn PeRekonomIAn UmAt - Al Arif, M Nur Rianto (ULUL ALBAB Jurnal Studi Islam, 2013)
The government poverty alleviation program could not give a significant change to reduce poverty. It needed a support from other sub-system, such as zakah. Zakah, as one of the Islamic fiscal instruments has played a significant role in Islamic economic. The potential of zakah would cover several aspects like poverty alleviation program through social welfare system. Zakah could obtain a social welfare system such as workplace accident insurance, old age pension, pension insurance, and death insurace. In addition, other problems such as housing for the poor, capital investment and education could be cared through zakah if zakah was managed and developed in a maximal way.